Perceived stress and anxiety in government employees during remote work arrangements : A correlation study - Myra Dela P. Oruga; Jessica Mae D. Viray-Inciong; Laili Rahayuwati (Jurnal Keperawatan Padjadjaran, 2025)
Background: The transition to remote work has significantly reshaped workplace structures, posing unique challenges for employees. Government workers, accustomed to face-to-face interactions, faced substantial adjustments when transitioning to remote arrangements, leading to concerns about their mental health, particularly stress and anxiety. Purpose: This study examines perceived levels of stress and anxiety among government employees in remote work arrangements and investigates the relationship between these mental health outcomes and socio-demographic factors. Methods: A descriptive correlational study design was employed, targeting 257 government employees from 11 PhilHealth offices in the National Capital Region. Stratified random sampling recruited 173 employees completing an online self-administered survey. The Perceived Stress Scale (PSS-10) and Generalized Anxiety Disorder Assessment (GAD-7) tools were used to measure stress and anxiety levels. Descriptive statistics and Chi-Square tests were applied for data analysis. Results: Most respondents (96.32%) reported moderate stress levels (mean PSS score = 19.51), while nearly half (49.69%) exhibited mild anxiety (mean GAD-7 score = 6.83). Severe stress and anxiety were minimal, at 3.07% and 0.61%, respectively. No significant correlations were identified between socio-demographic factors and mental health outcomes. Conclusions: The study highlights moderate stress and mild anxiety levels among government employees during remote work. Findings emphasize the importance of mental health support and structured remote work policies to address workplace stress during periods of significant organizational change.